The Application of Shape Language in Komodo Character Design for the IP FANI “Indonesian Children's Fable” - Rita Kemalasari; Nuria Indah Kurnia Dewi; Cora Emilia Malikiyano (Institut Seni Indonesia Yogyakarta, 2026)
This research aims to create a character design strongly infused with Nusantara local icons, which will become part of the FANI (Fabel Anak Indonesia/Indonesian Children's Fable) IP, given the significant audience demand for educational content among early childhood. Based on these criteria, one of the Nusantara endemic animals, the Komodo dragon, was selected to be part of the FANI IP and is realized as two twin Komodo children characters,